Effects of cell cycle phases on the induction of dental pulp stem cells toward dopaminergic‐like cells. (7th July 2017) - Gnanasegaran, Nareshwaran; Govindasamy, Vijayendran; Kathirvaloo, Premasangery; Musa, Sabri; Abu Kasim, Noor Hayaty
Abstract: Parkinson's disease (PD) is characterized by tremors and cognitive issues, and is due to the death of dopaminergic (DA‐ergic) neurons in brain circuits that are responsible for producing neurotransmitter dopamine (DA). Currently, cell replacement therapies are underway to improve upon existing therapeutic approaches such as drug treatments and electrical stimulation. Among the widely available sources, dental pulp stem cells (DPSCs) from deciduous teeth have gained popularity because of their neural crest origin and inherent propensity toward neuronal lineage. Despite the various pre‐clinical studies conducted, an important factor yet to be elucidated is the influence of growth phases in a typical trans‐differentiation process. This study selected DPSCs at three distinct time points with variable growth phase proportions (G0/G1, S and G2/M) for in vitro trans‐differentiation into DA‐ergic‐like cells. Using commercially available PCR arrays, we identified distinct gene profiles pertaining to cell cycles in these phases. The differentiation outcomes were assessed in terms of morphology and gene and protein expression, as well as with functional assays. It was noted that DPSCs with the highest G0/G1 phase were comparatively the best, representing at least a 2‐fold up regulation ( p  < 0.05) of DA‐ergic molecular cues compared to those from the remaining time points. Further investigations in terms of protein expression and DA‐release assays also revealed a similar phenomenon ( p  < 0.05). These findings are expected to provide vital information for consideration in improving standard operating procedures in future cell transplantation work. Copyright © 2017 John Wiley & Sons, Ltd.